Trochlear Dysplasia and Its Structural Correlates on Knee Magnetic Resonance Imaging: A Multiparametric Analysis - Timoçin Yığman, Gizem; Özen Atalay, Hande (The European Research Journal, 2026)
Objectives: To investigate associations between trochlear dysplasia severity and various morphometric and degenerative findings on knee Magnetic Resonance Imaging (MRI) Methods: A total of 211 knee MRIs from 181 patients diagnosed with trochlear dysplasia between November 2012 and March 2025 were retrospectively reviewed. Morphometric parameters - sulcus angle, trochlear depth, tibial tuberosity to trochlear groove (TT-TG) distance, patellar angle, and patellar position - were measured. Chondromalacia patella (grades 0-4), meniscal degeneration and tear, and Anterior Cruciate Ligament (ACL) mucoid degeneration were also recorded. Statistical analyses included ANOVA, Kruskal–Wallis, and chi-square tests. Results: Trochlear dysplasia type A was the most common (61.1%). Significant associations were found between trochlear dysplasia severity and sulcus angle, TT-TG distance, and trochlear depth (P